1998
DOI: 10.1086/515591
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic Responses Associated with 12 Weeks of Combination Antiretroviral Therapy Consisting of Zidovudine, Lamivudine, and Ritonavir: Results of AIDS Clinical Trials Group Protocol 315

Abstract: Human immunodeficiency virus (HIV)-1 infection is associated with progressive cell-mediated immune deficiency and abnormal immune activation. Although highly active antiretroviral therapy regimens can increase circulating CD4 T lymphocyte counts and decrease the risk of opportunistic complications, the effects of these treatments on immune reconstitution are not well understood. In 44 persons with moderately advanced HIV-1 infection, after 12 weeks of treatment with zidovudine, lamivudine, and ritonavir, plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
242
2
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 397 publications
(264 citation statements)
references
References 37 publications
18
242
2
2
Order By: Relevance
“…Several studies have reported increased rates of viral replication and decreases in TCD 4 + cell counts during acute phases of TB [13,[48][49][50][51]. TCD 8 + cell counts had lower values in patients with disseminated TB at study entry; however, the differences were not significant.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Several studies have reported increased rates of viral replication and decreases in TCD 4 + cell counts during acute phases of TB [13,[48][49][50][51]. TCD 8 + cell counts had lower values in patients with disseminated TB at study entry; however, the differences were not significant.…”
Section: Discussionmentioning
confidence: 94%
“…It is known that M. tuberculosis activates HIV expression [49], and that it may increase pathogenicity and speed up disease progression to AIDS [13].…”
Section: Discussionmentioning
confidence: 99%
“…Co-expression of CD45RA and CD62L was used to identify the naive T cell subsets. 6,57 At baseline, the median number of CD45RA and CD62L positive (naive) CD4 T cells was 19.5 cells/ml (range 2 ± 392, standard error 37.4), which increased to 114 (range 5 ± 346, standard error 35.3) at day 60 (overall P=0.02). At day 180, median 58.5 (range 13 ± 113, standard error=11.9) naive CD4 T cells/ml were present.…”
Section: Immune Reconstitution Following Therapymentioning
confidence: 98%
“…For example, it is not known whether the recovery of CD4 cells is purely a consequence of viral load suppression or that ART (or different ART regimens) may impact CD4 directly or through other pathways. 20 Our primary aim is to model the trajectories of CD4 over time as a function of the type of ART received and viral load. We use regression models to investigate the association between ART and CD4 restoration, while adjusting the possible impact of the antiviral effect.…”
Section: The Dataset and Research Objectivesmentioning
confidence: 99%